answersLogoWhite

0


Best Answer

y=4

User Avatar

Wiki User

6y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is the value of x when y 4 in the equation y 6x - 20?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the value of x in the following equation 6x plus 4 equals 60-2x?

6x + 4 = 60 - 2xSubtract 4 from each side of the equation:6x = 56 - 2xAdd 2x to each side:8x = 56Divide each side by 8:x = 7


What 6x plus 3 equals 4x plus 11?

It is an equation and the value of x is 4


Rewrite standard form equation into slope intercept equation y 6x-4?

10


The equations of two lines are 6x-y equal 4 and y equal 4x plus 2. What is the value of x in the solution for this system of equation?

You are given Y. Insert into first equation. 6X - (4X + 2) = 4 2X + 2 = 4 X = 2 ======= The value of X


Which is an equation of the line parallel to y 6x - 4 and passing through -3 -8?

If you mean: y = 6x-4 then the parallel equation is y = 6x+10


Find the value of x in the equation 6x plus 4 70-x equals 300?

x=10


What is the value of x in the equation 2x plus 17 equals 6x-23?

2x+17=6x-23 23+17=6x-2x 40=4x x=40 / 4 therefore x=10


What is the value of x in the equation 4x - 20 equals -4?

4x - 20 = -44x = 16x = 4


What is x when 12 plus 2x equals 6x-18?

12+2x = 6x-18 12+18 = 6x-2x 30 = 4x Divide both sides of the equation by 4 to find the value of x: x = 7.5


What is 6x-4 equals 20?

4


What is -6x plus 3y equals -18 -10 plus 5y equals -30 using substitution?

The question is not quite clear, do you mean -6x+3y = -18 and -10+5y = -30? If so then the solution is: -10+5y= -30 5y = -30+10 5y = -20 y = -4 Substitute the value of y into the equation -6x+3y = -18: Answer: x = 1 and y = -4


6x plus 4-3x?

To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.